Calibration updates in Minerva TB2 detector as a reference work for future tunings in neutrino detectors - Chavarría Rodríguez, Alberto Edgar (2018)
In the Neutrino Physics Field, a lot of careful measurements am made such as : cross section measure¬ment, neutrino oscillation, atmospheric neutrino. Etc. In such experimental measurements one has to get the most accurate numbers as possible but in doing so one meets a lot of constraints and variables. Such is the case of the Test Beam detector (a replica of the full MIN HR//A detector where we lest and compare new targets and devices to put them further in the MINERr/A detector). The way we detect some signal in the detector is by using a scintillator material attached to a photomultiplier (when a charged particle passes through the scintillator, this emits a photon of certain spectra and this light works as input for the PMT which uses the photoelectric effect to magnify the signal (gain)), in the same way the PMT is wired to the Data Acquisition System (DAQ) in order to process the raw data to give some human-readable numbers. In ideal laboratory conditions, one would expect to get accurate results just by carefully mount the electronics and understand the theory good enough. But nature likes to fool scientists. While making experiments involving fundamental particles, one uses electronic devices that have quantum and technological limita¬tions. One should not miss the effect of variables such as: temperature, moisture, dark current, etc that could impact over our data. In this work, it was explicitly studied the effect of temperature over a spe¬cial kind of data called Light Injection, which is a type of data used for calibration puiposes. Data was taken in two separate time intervals: April and May-July (2015 data already calibrated) which in between was a shutdown period (sometimes a temporal shutdown is done because cooling purposes, repairs in soft- w are/hard ware, etc). Two "thermometers" were used to get the temperature. One was a thermometer placed near the Test Beam IXtector. The other one is a chip built-in the PMT so that it can tell the temperature at all times. The first thermometer was used as a first approximation assuming that everything in the Test Beam IX tec tor was in thermal equilibrium. The second thermometer that was used shows a more realistic distribution of temperatures throughout the time the data was taken. Finally, plots of Gain vs Temperature are shown. These plots, indeed, tell the tempera turn effect over the data that was considered in this work. However, this temperature effect over the data was in principle ignored by the manufacturer because by- dealing w ith big amounts of data, one notices that this effect causes a decrease of less than 1% in gain of the data analyzed. Nevertheless, in high-accurate measurements this effect should not be neglected if one pursuits to get as close as possible to that number that nature tries to hide.